The Association between Serum Procalcitonin and Periodontitis in Type 2 Diabetic Patients on metformin in Baghdad / Iraq - Hameed, Zahraa; Omran , Alaa (Iraqi Journal of Pharmaceutical Sciences, 2023)
Among the most common conditions that affects teeth, periodontitis leads to destruction of the supporting apparatus of tooth structure. Procalcitonin (PCT) may be a helpful marker to determine the severity of infection, forecast the prognosis, and track the effectiveness of treatment. Aim of the study was to assess the association between the body's blood PCT level and periodontal bacterial infections in diabetic individuals on metformin treatment of 1000 mg dosage per day and contrasting it with non-diabetic people. A case control study conducted at the department of periodontics during a period from February to May 2022. It included 70 subjects divided into four groups according to periodontitis and diabetes (20 control and 50 patients) with matched age and gender. Assessment of clinical periodontal parameters (BOP, PLI, PPD, CAL) was done for each individual. Five ml of venous blood was taken from each participant for the quantitative determination of serum PCT and measurement of HbA1c. PCT was measured using ELISA technique.In this study serum PCT was significantly lower in controls than that in other groups and significantly lower in GP group than that in T2DM and T2DM+ GP groups. There was a significant strong positive correlation between serum PCT and HbA1c, and a positive non-significant correlation with periodontal parameters.In conclusion, an elevated blood PCT level has been proposed as a possible biomarker for periodontal disorders because it plays a role in periodontal inflammation. Additionally, subclinical, low grade chronic inflammation in diabetic individuals may be mediated by serum PCT, a possible proinflammatory mediator.